Need analysis for content development to improve quality in research / Muhammad Shahbaz Arif - Arif, Muhammad Shahbaz (Penerbit UiTM (UiTM Press), 2008)
The aim of the study is to examine the issues and current practices of the doctoral students of 12 universities spread all over Pakistan who are conducting their research. The research issues of the study are whether or not the doctoral students know various stages of the research such as proposal, introduction, literature review, methodology, results and discussion from the very beginning of the research. It was an experimental study over a span of one month held in 2006. The data were collected from 27 experienced university teachers selected randomly. First, the subjects were examined in the beginning of the Research Methodology Workshop, and later after a month on the completion of the Workshop held at Higher Education Commission, Islamabad. The results have shown a significant difference in the current practices and quality of research before and after the workshop.